AVIATION SECURITY: DEVELOPMENT OF ADMINISTRATIVE AND LEGAL ALGORITHMS - Betskov, Aleksandr; Melekhin, Aleksandr; Mazur, Sergey; Mironov, Anatoliy; Kilyaskhanov, Hizri; Vasiliev, Fedor; Gaponenko, Vladimir; Savchenko, Lyubov (Revista Inclusiones, 2019)
The purpose of the article is the analysis of the development of administrative and legal algorithms for an aviation security system. The article shows the relevance of improving the effectiveness of aviation security, analyzes the legal framework of aviation security at the Russian and international levels and substantiates the participation of internal affairs agencies in ensuring aviation security. The authors have proposed new approaches to the formation of a unified system for search and rescue of aircraft and spacecraft.